2012
DOI: 10.1002/da.21970
|View full text |Cite
|
Sign up to set email alerts
|

Extended Release Quetiapine Fumarate in Major Depressive Disorder: Analysis in Patients With Anxious Depression

Abstract: Quetiapine XR monotherapy improved symptoms of depression in patients with higher and lower levels of anxiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 37 publications
1
14
0
2
Order By: Relevance
“…In contrast to the many psychopharmacologic treatment studies that have evaluated adult patients with “anxious depression,” 8083 pediatric studies have largely focused on patients with depression or anxiety (eg, social phobia, separation anxiety disorder, GAD, or the combination) and have generally excluded anxious patients with comorbid MDD. 8488 Abundant evidence suggests that selective serotonin reuptake inhibitors (SSRIs) are effective in treating both pediatric MDD and anxiety disorders, 8991 and, on the basis of randomized controlled trials of SSRIs and selective serotonin norepinephrine reuptake inhibitors (SNRIs) (Table 1), recommendations can be extrapolated regarding the treatment of anxious depression in pediatric patients.…”
Section: Psychopharmacologic Treatment Of Anxious-depression In Youthmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the many psychopharmacologic treatment studies that have evaluated adult patients with “anxious depression,” 8083 pediatric studies have largely focused on patients with depression or anxiety (eg, social phobia, separation anxiety disorder, GAD, or the combination) and have generally excluded anxious patients with comorbid MDD. 8488 Abundant evidence suggests that selective serotonin reuptake inhibitors (SSRIs) are effective in treating both pediatric MDD and anxiety disorders, 8991 and, on the basis of randomized controlled trials of SSRIs and selective serotonin norepinephrine reuptake inhibitors (SNRIs) (Table 1), recommendations can be extrapolated regarding the treatment of anxious depression in pediatric patients.…”
Section: Psychopharmacologic Treatment Of Anxious-depression In Youthmentioning
confidence: 99%
“…It is interesting that post-hoc analyses of trials with both aripiprazole and quetiapine have suggested that these agents may have efficacy for anxious depression. 83,131 However, use of second-generation antipsychotic medications has been associated with significant adverse effects, including weight gain, diabetes or insulin insensitivity, dyslipidemia, and potential tardive dyskinesia. Thus, the risk and benefits of any medication changes should be weighed to ensure optimal therapeutic outcomes.…”
Section: Psychopharmacologic Treatment Of Anxious-depression In Youthmentioning
confidence: 99%
“…Symptom severity, clinical course/outcome and functioning may be worse in patients with atypical/anxious depression than in those without [43,44]. According to retrospective analyses of pooled data of aripiprazole and quetiapine XR, they may be effective and reliable augmentation agents for patients with MDD regardless of the presentation of subdepressive symptoms, depression severity, past treatment response, or previous antidepressant treatment failure [45][46][47][48][49]. No clinical factors predicting response to augmentation antipsychotics have been found in patients with MDD.…”
Section: Clinical Issues In the Use Of Atypical Antipsychotics In CLImentioning
confidence: 99%
“…(Ionescu et al, 2014) Although treatment with serotonergic antidepressants (e.g., selective serotonin reuptake inhibitors (SSRIs), serotonin-norepinephrine reuptake inhibitors (SNRIs), and tricyclic antidepressants (TCAs)) can result in initial treatment success in some cases, patients with anxious depression can often require second- and third-line therapy in order to achieve sustained response or remission. (Ionescu et al, 2014, Wiethoff et al, 2010, Wu et al, 2013a) Furthermore, anxious depression puts patients at a higher risk than those without anxious depression for suicidal thinking and attempts (Fava et al, 2008, Seo et al, 2011) and side-effects,(Ionescu et al, 2014, Chan et al, 2012, Thase et al, 2012, Farabaugh et al, 2012, Fava et al, 2008, Wu et al, 2013b) which contribute to overall poorer treatment outcomes. (Ionescu et al, 2014, Farabaugh et al, 2012, Fava et al, 2008, Wiethoff et al, 2010, Wu et al, 2013b, Thase et al, 2012)…”
Section: Introductionmentioning
confidence: 99%